ANTARA TEORI FORMULA ALBERT B LORD DAN MUSIKOLOGI - Widyanta, Nugrahanstya Cahya (Institut Seni Indonesia Denpasar, 2018)
Study of oral literature and a discipline named musicology have a linkage that has never been very often expressed yet. This paper is to reveal that music is an oral frame to bring a regularity in making sentences of oral literature  works in Yugoslavia. Such a thing is researched using a qualitative method. Data analysis is done through three steps, they are data reduction, data display, and conclusion and verification. The data is taken from a book entitled The Singer by Albert B Lord containing his theoretical formula concerning the oral literature in Yugoslavia. It is analysed by using a theory of musical form and structure by Leon Stein. Compositions in the oral literature is seen using Lord?s theory of formula. In this case, a singer remembers the repetition and creates it by analogy by the way of repeating  the existing words, phrases, clauses, and arrays. There is a process of re-accumulating,  re-combinating, and re-modelling the existing formula. So, the singer has his or her own style in expressing the works of the oral literature, but he or she always has the same number of syllables in every sentence. This can happen due to the musical taste used. The singer never count the number of syllables that exists but such regularity can occur due to the musical taste.